Vampire vigilantes the fall of the house of blodvat - Cox, Michael; Smedley, Chris (Hodder Children's London, 2002)
"After a narrow escape from capture by the dastardly vampires, the vigilantes can at last piece together their enemy's wicked plans. The recent horrors of Hallowe'en (see book 2: Nightmare on Eck Street) are nothing compared with what lies ahead for the residents of Chumley and indeed all of Britain. For quietly, carefully, the vampires are awaiting the Return of the Master"--Amazon